(untitled) (Journal of Asian Geography, 2022)
When an anthropologist discusses the concept of change in society, he typically refers to changes that are regarded as profound. The process that brings about the change encompasses a lengthy period of time, which the vast majority of society does not typically recognise. The majority of significant changes are typically caused by cultural contact, particularly the influence of large civilisations on small communities. Recent colonisation and international trade activities have resulted in the convergence of diverse cultures. Typically, these encounters result in the transformation of cultures that are subjugated or controlled in some way. The Malay culture is one example of a society that has undergone such transformations in the last thousand years or more. Malaysian society is a relatively recent historical phenomenon. Several Malay communities along the Kelantan River in Kota Bharu, Kelantan, were chosen for the research. This study’s purpose is to examine the effects of the destruction of Malay settlements and the transformation of Malay transportation. A total of 350 respondents were chosen at random and supported by interviews, observation, and visual analysis to generate a discussion of the study. Destruction of Malay settlements and changes in transportation have contributed to the vulnerability of Malay identity in the face of urban experience.